Gendered impacts of conservation agriculture: Evidence of empowerment and constraint from Northwestern Ghana - Suleman, Sufyan (International Journal of Sustainable Agricultural Research, 2026)
Across sub-Saharan Africa, women serve as key actors in smallholder agricultural production. However, they face gendered inequalities in land access, knowledge, labor, and farm and household decision-making, which continue to impede their capacity to benefit from innovative agricultural interventions such as conservation agriculture (CA). This research assesses how women are empowered through resource access, household decision-making power, workload dynamics, control of income, food security, and psychosocial achievement through their participation in the Ghana Agricultural Sector Investment Programme’s Conservation Agriculture (GASIP-CA) in northwestern Ghana. The study employed a mixed-method research approach, comprising a survey of 180 beneficiary women farmers, 6 focus group discussions, and 10 key informant interviews. The study found that GASIP-CA has significantly improved women's access to resources through capacity-building training on CA principles and access to labor-saving technologies. But structural challenges such as insecure land access persisted. There have been improvements in women’s agency in household and community decision-making dynamics, as many reported training men on CA principles. Women also made significant achievements in terms of improved income and savings, food security, self-esteem, soil fertility, and household cohesion. Therefore, it was concluded that CA interventions can play a central role as a multidimensional empowerment pathway for addressing gendered disparities in land access, household decision-making dynamics, and labor dynamics. Agricultural policies and programs should target secure land and other resource access, leadership, and capacity-building opportunities for women as a basis for their empowerment.